Comparison of treadmill and simultaneous arm and leg ergometry in VO2MAX analysis - Kostuck, J. A.; Selland, C. A.; Frost, J. M. (International Journal of Sports Science, 2020)
Maximal oxygen consumption (VO2MAX) testing can be performed on a variety of modalities ranging from treadmills to rowing ergometers. The purpose of VO2MAX testing is to determine a person's aerobic capacity and has been shown to elicit the highest response in treadmill (TM) testing. Very few studies have examined the idea of incorporating arm cycling combined with leg cycling in VO2MAX testing. The purpose of this study was to compare a simultaneous arm and leg ergometry (SALE) testing protocol to a TM VO2MAX test. Forty-seven college-aged individuals (female: n=27) volunteered for this study, completing both TM and SALE VO2MAX tests. VO2MAX was higher for TM than SALE (45.6 ± 8.7 vs. 41.0 ± 8.0 ml/kg/min, respectively; p 2MAX test was longer for TM than SALE (11.1 ± 2.1 vs 7.9 ± 3.2 min, respectively; p r = 0.92). Heart rate at VO2MAX (p = 0.31), was not different between tests. The ratio of SALE/TM results ranged from 68.9-104.6%. VO2MAX values were more similar for females than males (F(1, 45) = 5.08, p = 0.03). The main finding is the addition of arm-ergometry to leg-ergometry produced lower VO2MAX and test length compared to a treadmill test. Future research should look into modifying the resistances of the SALE protocol to be adapted to the subject's body weight and fitness level to determine if this elicits a higher VO2MAX.